Pengaruh Ukuran Perusahaan, Debt To Equity Ratio, Debt To Asset Ratio dan Risk Based Capital Terhadap Profitabilitas (Studi Empiris pada Perusahaan Asuransi Umum Unit Usaha Syariah Tahun 2014-2018) - Lulu Mardhiyah Sayekti; Suryo Budi Santoso (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2020)
The purpose of this study is to determine the effect of company size , debt to equity ratio, debt to asset ratio and risk based capital towards profitability. The research periods used are during 2014-2018. This research is a quantitative study that uses secondary data and was obtained by documentation and literature study techniques. Sampling was carried out using a purposive sampling method in which 70 research samples were obtained at general insurance companies of sharia business units registered at the Financial Services Authority (OJK) during  2014-2018. The analytical method used is multiple linear regression analysis. The results of this study showed that company size has a positive effect on profitability. Debt to equity ratio has a negative effect on profitability. Debt to asset ratio has no effect on profitability. Meanwhile, risk based capital has a negative effect on  profitability.